Z-score:Solusi Praktis Untuk Mengukur Stabilitas Perusahaan: Z-score - Reynaldi surya saputra; Nur Fitriana, SE.,M.Ak; Yusufi febran aldiansyah; Fakhrul ilham; Marcel muliano suatan; Muhammad hanif (Jurnal Akuntansi, Bisnis dan Ekonomi Indonesia (JABEI), 2025)
financial stability is critical for corporate longevity in today’s dynamic business environment. This study investigates the practical application of the Altman Z-Score model as an early warning system for predicting financial distress in Indonesian firms. A descriptive-analytical approach utilizing a systematic literature review was employed to examine empirical studies published over the last decade. Key findings demonstrate that the original and modified Z-Score models achieve high predictive accuracy—averaging 87.5% in the hospitality and tourism sector and exceeding 80% in manufacturing—when classifying companies into safe, grey zone, and distress categories. However, accuracy varies by industry and period, highlighting the need for coefficient adjustments or additional variables tailored to Indonesia’s market conditions. Limitations of the Z-Score, including its inapplicability to start-ups and firms with prolonged losses, and its exclusion of qualitative factors, are discussed. The study concludes that while the Altman Z-Score is a valuable, objective tool for financial risk assessment, it should complement rather than replace comprehensive financial analysis. Future research should focus on locally calibrated models that integrate macroeconomic and qualitative indicators..